Comparing Time-Use Estimates of Two Different Time Diary Methods - Hossein Sourtiji; Mehdi Rassafiani; Seyed Ali Hosseini; Mohammad Esmaeil Motlagh; Mehdi Noroozi (Iranian Rehabilitation Journal, 2018)
Objectives: Time-use has become an important field of research in social and medical sciences. Time diary is the most popular method for measuring time-use that has 2 different methods of administration including yesterday and tomorrow diary. The present study aimed to compare these methods of measuring time-use. Methods: This cross-sectional comparative study was conducted on 256 under 5-year-old healthy children that were selected using multistage stratified cluster sampling method in 2017. Data were analyzed using Kolmogorov-Smirnov Test, Pearson correlation coefficient, Spearman correlation coefficient, 2-way ANOVA, Independent t-test and Mann–Whitney U Test. Results: Participants spent 1476.23 min/d on aggregate daily occupations, according to the yesterday-diary estimate, and 1492.14 min/d according to the tomorrow-diary. In one area of occupation, the yesterday and tomorrow diary estimates differed slightly. Two-way ANOVA found no significant interaction between diary method and age category (F5,234=1.222, P=0.300) and no significant main effect of diary method (F1,234 =0.830). While, the ANOVA revealed a significant main effect for age category (F5,234=4.91, P=0.00). There were no significant mean differences in the number of occupational repertoires between the participants of yesterday and tomorrow diary groups. Likewise, there were no significant differences in the number of verbatim of the two groups. Discussion: The findings of our study indicated no difference between yesterday and tomorrow diaries estimates in terms of measuring under 5-year-old children’s time-use.